1983
DOI: 10.1111/j.1365-2672.1983.tb02630.x
|View full text |Cite
|
Sign up to set email alerts
|

Phages naturally associated with the aizawai variety of insect pathogen Bacillus thuringiensis and their relevance to strain identification

Abstract: Of 36 strains of the ‘aizawai’ variety of Bacillus thuringiensis (H‐serotype 7) 16 were naturally associated with bacteriophages, 11 of which were isolated at titres of 106 plaque‐forming units/ml and above. These 11 phages had varied host ranges among Bacillus cereus and five strains of the ‘aizawai’ variety of B. thuringiensis. Host range, plaque morphology and differences in cold lability indicated dissimilarities between the phages, which could be used taxonomically to differentiate between strains of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Past surveys of strains of B. thuringiqzsis have suggested that a significant proportion harbour one or more temperate phages (Colasito & Rogoff, 1969;Ackermann & Smirnoff, 1978;Jones et al, 1983). However, the physical characteristics of these phages, as well as their relationships with the host strains, have not been examined in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past surveys of strains of B. thuringiqzsis have suggested that a significant proportion harbour one or more temperate phages (Colasito & Rogoff, 1969;Ackermann & Smirnoff, 1978;Jones et al, 1983). However, the physical characteristics of these phages, as well as their relationships with the host strains, have not been examined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Since this commercially important species has only limited means of genetic exchange, temperate phages could be important genetic tools, serving as mediators of generalized and specialized transduction and as potential cloning vehicles. We have thus been interested in the characterization of temperate phages from this species.Past surveys of strains of B. thuringiqzsis have suggested that a significant proportion harbour one or more temperate phages (Colasito & Rogoff, 1969;Ackermann & Smirnoff, 1978;Jones et al, 1983). However, the physical characteristics of these phages, as well as their relationships with the host strains, have not been examined in detail.…”
mentioning
confidence: 99%
“…Bacteriophages are associated with most strains of Bacillus thuringiensis (Martin & Dean 1981). These phages may be virulent (Colasito & Rogoff 1969a;Ackerman & Smirnoff 1974) or temperate (Colasito & Rogoff 1969b;de Barjac et al 1974;Ackermann & Smirnoff 1978;Martin 1979;Azizbekyan et al 1980;Vasantharayan & Munirathnama 1980;Landen et al 1981;Jones et al 1983).…”
mentioning
confidence: 99%
“…Most phages infecting B. thuringiensis and B. sphaericus were studied as viruses or for phage typing of bacteria. ( COLASTIO and ROGOFF 1969a, b;AZIZBEKIAN and NETYKSA 1978a;BOGUSH et al 1978;JONES et al 1983;YOUSTEN 1984). Meanwhile, the interrelationships between the entomobacilli and their specific phages were extended to be utilized in molecular biology, and genetic engineering ( LECADET et al 1980;LANDEN et al 1980;HEIERSON et al 1983).…”
Section: Introductionmentioning
confidence: 99%